2017
DOI: 10.3389/frobt.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Mixed Reality for Manufacturing Training

Abstract: In complex manufacturing a considerable amount of resources is focused on training workers and developing new skills. Increasing the effectiveness of those processes and reducing the investment required is an outstanding issue. In this paper, we present an experiment (n = 20) that shows how modern metaphors such as collaborative mixed reality can be used to transmit procedural knowledge and could eventually replace other forms of face-to-face training. We implemented a mixed reality setup with seethrough camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Several studies have been conducted to evaluate the influence of VR on training outcomes, and empirical reports have showed heterogeneous results (Dubovi et al, 2017;Gonzalez-Franco et al, 2017;Makowski et al, 2017;Jung and Ahn, 2018;Makransky et al, 2019). Logishetty et al (2019) found that surgeons trained using VR were more accurate in performing a total hip arthroplasty procedure compared to those that had undertaken the standard training.…”
Section: Vr Technology In Trainingmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the influence of VR on training outcomes, and empirical reports have showed heterogeneous results (Dubovi et al, 2017;Gonzalez-Franco et al, 2017;Makowski et al, 2017;Jung and Ahn, 2018;Makransky et al, 2019). Logishetty et al (2019) found that surgeons trained using VR were more accurate in performing a total hip arthroplasty procedure compared to those that had undertaken the standard training.…”
Section: Vr Technology In Trainingmentioning
confidence: 99%
“…They concluded that an augmented reality platform was more suitable for training of this type of tasks and encouraged further evaluation of virtual reality based training. In a more recent study Gonzalez-Franco et al compared collaborative conventional face-to-face training with a mixed reality training setup for a manufacturing procedure of an aircraft door [6]. Their results indicated that performance levels yielded by the immersive mixed reality training system were not significantly different from the conventional face-to-face training format.…”
Section: Related Workmentioning
confidence: 99%
“…However, this needs to be taken into account, as using Unity might increase the latency. Nevertheless, we believe that using an interfacing program such as Unity would be a normal use to access the cameras and produce synthetic video for future rendering of see-through and mixed reality systems that combine both video and synthetic content [26,51].…”
Section: Devicesmentioning
confidence: 99%
“…We use video see-through AR devices for multiple reasons: (i) they provide access for good hardware instrumentation-based measurements to have robust system comparisons; (ii) they enable an AR experience while enjoying the field of view of VR [9] in which we can blend with a real world view [26,30,56] and modify its content if required [51].…”
Section: Introductionmentioning
confidence: 99%